Exploration of the Need for Nursing Human Resources Information Systems for Geographical Mapping of Nurses: A Qualitative Study - Ibnu Rusdi; Budi Anna Keliat; Rr. Tutik Sri Hariyati; Yudho Giri Sucahyo (GLOBAL HEALTH SCIENCE GROUP, 2022)
The existence of data discrepancies related to nursing human resources requires an integrated Nursing HR Information System between interested parties (stakeholders). The purpose of this study is to explore the needs of nursing human resource management information systems. This qualitative research uses a phenomenological approach. Data collection uses in-depth interview techniques with open ended questions, which are carried out online and offline. The research was located at the Bogor Regency Health Office, Depok City Health Office, Cibinong Hospital Bogor Regency, Depok City Hospital, Karadenan Health Center and Bojonggede Health Center in Bogor Regency, Kemiri Muka Health Center and Sawangan Health Center in Depok City. Participants consisted of Health Human Resources Managers, Nursing Human Resources Managers, Nurses in Hospitals, Nurses at Puskesmas and Administrators of Nursing Profession organizations with a total of 28 participants. Data analysis uses a systematic coding process. The results of the study found three themes, namely the components of the information system, the features of the information system and the information produced. Participants expressed needs that would be basic input or data in the development of a geographic-based nursing human resource information system model.